2016
DOI: 10.3989/scimar.04435.25a
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic discrimination factors and nitrogen turnover rates in reared Atlantic bluefin tuna larvae (<em>Thunnus thynnus</em>): effects of maternal transmission

Abstract: Summary:The use of stable isotope analysis to study animal diets requires estimates of isotopic turnover rates (half time, t 50 ) and discrimination factors (Δ) for an accurate interpretation of trophic patterns. The stable isotopes of carbon and nitrogen were analysed for eggs and reared larvae of Thunnus thynnus, as well as for the different diets supplied during the experiment. The results showed high values of δ 15 N in eggs and larvae (n=646) until 4 DAH. After this time lapse, the stable isotope values d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 66 publications
6
30
0
Order By: Relevance
“…Δ 15 N bulk values of T. thynnus during the early larval stage were higher than those of tuna species at the same stage. We applied the maternal isotopic transmission model to these preflexion larvae to estimate maternal isotopic signatures (Uriarte et al 2016) and found the N isotopic values estimated (mean ± SD: 12.11 ± 1.83 ‰) were similar to those reported for adult T. thynnus in the GOM spawning area (approx. 11 to 13 ‰; see Butler et al 2015, Logan et al 2011.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Δ 15 N bulk values of T. thynnus during the early larval stage were higher than those of tuna species at the same stage. We applied the maternal isotopic transmission model to these preflexion larvae to estimate maternal isotopic signatures (Uriarte et al 2016) and found the N isotopic values estimated (mean ± SD: 12.11 ± 1.83 ‰) were similar to those reported for adult T. thynnus in the GOM spawning area (approx. 11 to 13 ‰; see Butler et al 2015, Logan et al 2011.…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, ontogenetic differences in SIA bulk values between pre-and postflexion tuna larvae are likely a result of maternal transmission of isotopes (Uriarte et al 2016). Δ 15 N bulk values of T. thynnus during the early larval stage were higher than those of tuna species at the same stage.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations